Composition and diversity of riparian vegetation of the Talau river, Belu Regency - Vebronia Liunima; Leonardus Banilodu; Chatarina Gradict Semiun (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
Riparian vegetation has a very important ecological role i.e. maintaining water quality, as a supplier of litter, as a habitat, and as a natural filter for various pollutants. Riparian vegetation is found along the side of the river, such as along the Talau, Belu river. The purpose of this study was to determine the composition and diversity of riparian vegetation. The research area consisted of three riparian types, namely teak plantations (A Station), mixed forest (B Station), and processed land (C Station). The method used was the quadrant method. Determination of sample size was based on the species-area curve. Data were calculated using the Shanon-Wiener diversity index. The research results revealed that at A station there were 29 species consisting of 24 families; at B station there were 53 species consisting of 31 families, and at C station there were 25 species consisting of 21 families. The highest diversity (H') was found at station B with a good diversity category, followed by A station with medium and low categories, and C station with a low category.